NAVIGASI PARADIGMA DIGITAL: ANALISIS KOGNITIF PENGGUNAAN CAD, DESAIN PARAMETRIK, DAN AI DALAM PENDIDIKAN ARSITEKTUR - Muchlis, Nurfahmi; Irvansyah, Irvansyah; Krisdianto, Johanes; Kharismawan, Rabbani (Universitas Negeri Gorontalo, 2025)
The evolution of digital design tools from CAD and parametric design to Artificial Intelligence (AI) demands a fundamental shift in architectural pedagogy. However, the understanding of how these three function as an integrated ecosystem influencing students' cognitive processes remains limited. This study aims to bridge this gap through a mixed-methods study of 35 architecture students at the Sepuluh Nopember Institute of Technology (ITS). Using a three-stage design task instrument based on the work of Peter Eisenman, the research analyzes student performance quantitatively (scores) and qualitatively (design artifacts). The results show that students' highest capabilities lie in parametric design, with 89% achieving high scores, indicating a strong mastery of logical-procedural thinking. Conversely, AI poses the greatest cognitive challenge, with only 46% achieving high scores, not due to a lack of technical proficiency, but rather the difficulty in translating spatial concepts into linguistic articulation (prompts). This study concludes that each tool has unique and complementary pedagogical roles: CAD as the foundation of formal language, parametric design as a trainer for generative logic, and AI as a stimulator for conceptual articulation. The implication is that architectural curricula must evolve beyond mere software training to consciously cultivate these three modes of thinking in an integrated manner.